Exploring the Phytochemical Profile and Therapeutic Potential of Saudi Native Santolina chamaecyparissus L. Essential Oil - Hanan Y. Aati; Wedad Sarawi; Hala Attia; Rehab Ghazwani; Lama Aldmaine (Pharmaceutics, 2025)
Background/Objectives: Medicinal plants such as Santolina chamaecyparissus L., an evergreen shrub from the Asteraceae family, have long been valued for their bioactive compounds and traditional therapeutic uses. Materials: In this study, the essential oil of S. chamaecyparissus (EOSC) was isolated via hydrodistillation and then comprehensively evaluated for its phytochemical composition and antioxidant, anti-inflammatory, hemolytic, and cytotoxic properties, as well as its in silico bioactivity. Results: In total, 89.5% of the essential oil composition was successfully identified using GC-MS analysis. Hydrocarbon sesquiterpenes constituted the largest fraction (36.0%), followed by oxygenated sesquiterpenes (19.7%). Phytochemical screening revealed high phenolic content (839.50 ± 5.0 mg GAE/g E.O), while the Total Antioxidant Capacity (TAC) assay confirmed its strong antioxidant potential. The oil showed moderate hemolytic activity and significant lipoxygenase inhibition, indicating anti-inflammatory capability. The cytotoxic effects of the EOSC were evaluated using the MTT assay and HepG2 liver cancer cells. A dose-dependent reduction in cell viability was observed, confirming the oil’s strong anticancer activity. Molecular docking and ADMET analyses supported the bioactivity of the identified compounds, which showed good drug-likeness and pharmacokinetic properties. Conclusions: These findings demonstrate that EOSC has promising antioxidant and anti-inflammatory properties, suggesting that it could have potential as a safe natural substance for use in drug development and food preservation.